Evaluation of the blood ammonia level as a non-invasive predictor for the presence of esophageal varices and the risk of bleeding - , Asmaa Elzeftawy, Loai Mansour, Abdelrahman Kobtan, Heba Mourad, Ferial El-Kalla (Turkish Journal of Gastroenterology 1, 2019)
Background/Aims: The development of esophageal varices (EV) and resultant bleeding are the most critical complications of portal hypertension. Upper gastrointestinal endoscopy is the gold standard for diagnosis of EV. To find a non-invasive method for diagnosis of EV and to predict the bleeding risk is appealing and would decrease the cost and discomfort of upper endoscopy. The aim of our study was to evaluate the blood ammonia level as a predictor of the presence of EV and of a high risk of bleeding. Materials and Methods: In this cross-sectional study, a total of 359 patients with cirrhosis were examined for the presence of EV by upper endoscopy. Abdominal ultrasonography, calculation of the Child-Pugh score, and measurement of blood ammonia were performed for each patient. Results: The blood ammonia level was significantly higher in patients with EV than in those without it (p<0.001), and in patients with a high risk of variceal bleeding than in those with a low risk (p=0.026). Conclusion: An increased blood ammonia level and splenic vein diameter are predictors for the presence of EV and bleeding risk factors. The blood ammonia level may be clinically useful as it correlates with and is an independent predictor for both the endoscopic risk signs and risk factors of bleeding, and therefore, it could be used in patients with cirrhosis to decrease the number of screening endoscopies they are subjected to. Cite this article as: Elzeftawy A, Mansour L, Kobtan A, Mourad H, El-Kalla F. Evaluation of the blood ammonia level as a non-invasive predictor for the presence of esophageal varices and the risk of bleeding. Turk J Gastroenterol 2019; 30: 59-65.